Barrett’s Esophagus and Intestinal Metaplasia - Zhang, Lu; Sun, Binyu; Zhou, Xi; Wei, QiongQiong; Liang, Sicheng; Luo, Gang; Li, Tao; Lü, Muhan (Frontiers in Oncology, 2021)
Intestinal metaplasia refers to the replacement of the differentiated and mature normal mucosal epithelium outside the intestinal tract by the intestinal epithelium. This paper briefly describes the etiology and clinical significance of intestinal metaplasia in barrett’s esophagus. This article summarizes the impact of intestinal metaplasia on the diagnosis, monitoring, and treatment of barrett’s esophagus according to different guidelines. We also briefly explore the basis for the endoscopic diagnosis of intestinal metaplasia in barrett’s esophagus. The identification techniques of goblet cells in barrett’s esophagus are also elucidated by some scholars. Additionally, we further elaborate on the current treatment methods related to barrett’s esophagus.